PEMBERDAYAAN MASYARAKAT DI DESA MARGASARI KECAMATAN PASAWAHAN KABUPATEN PURWAKARTA BERBASIS KEAGAMAAN, PENDIDIKAN, DAN SOSIAL-BUDAYA - Firnando, Hero Gefthi; Ulya, Umniyyatul; Febrian, Rama Balka; Karima, Siti Ainul; Hidayatullah, Mohammad; Mufarokhah, Nova; Al-Aimin, Al-Aimin; Jannah, Junia Nur; Izzatullah, Husein Yusuf; Purwandi, Purwandi; Jamaluddin, Jamaluddin; An-Nuri, Qotrun Nada; Karbela, Rahayu Syahidah; Nuraeni, Siti; Arlan, Joni (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2024)
Community service through Student Community Service (KKN) in Margasari Village, Purwakarta, aims to empower the community through religious, educational, and socio-cultural approaches. This study identified several challenges in the village, including low levels of education, lack of awareness of environmental cleanliness, and declining spirit of mutual cooperation. An analysis of village conditions shows that most of the population works as farmers or factory workers. The long distance to high school is a barrier for some teenagers to continue their education. In addition, the presence of a final disposal site (TPA) in the village also affects the quality of the environment and public health. To overcome these problems, the community service program focuses on improving the quality of life of the community through various activities. These activities include religious education for youth, increasing awareness of the importance of education, and strengthening socio-cultural values such as mutual cooperation. The results of this program are an increase in the quality of human resources in Margasari Village, the realization of a clean and healthy environment, and the resurgence of the spirit of mutual cooperation in the community. Through an integrated approach between religion, education, and socio-culture, it is expected that this community empowerment program can make a significant contribution to village development.